Kinerja Keuangan Badan Layanan Umum RSUD dr. Soedomo Trenggalek dengan Metode Value for Money - Ketut Ayusia Madewi; Mahsina Mahsina; Arief Rahman (Universitas Bhayangkara Surabaya, 2023)
Hospital RSUD dr. Soedomo Trenggalek is a public service organization which provides services in the healthcare sector. BLUs financial management model is flexible. Therefore measuring financial performance is necessary. Value for money can be used to evaluate the use of an organizations budget in terms of efficiency and effectiveness in economic aspects. The research aims to analyze and to determine the financial performance of RSUD dr. Soedomo Trenggalek uses the value for money method for testing. This study uses a descriptive qualitative approach and data is collected from the 2018-2022 Budget Implementation Report. Measurement of quality-price ratio Dr. from the hospital. Soedomo Trenggalek is classified as very economical in terms of efficiency less efficient and effectiveness in terms of effective.